Perlindungan dan Tanggung Jawab Hukum Atas Pembatalan Transaksi Jual Beli Melalui Metode Cash On Delivery di E-Commerce - Kirana, Chandra; Yunanto, Yunanto (Fakultas Syariah INSURI Ponorogo, 2023)
The cash on delivery payment system makes it very easy for the community. However, it cannot be denied that online transaction cancellations occur in the cash on delivery (COD) system and have an impact on the parties involved: sellers, buyers, e-commerce and couriers. The aim of this research is to analyze legal protection and legal responsibility for canceling buying and selling transactions via cash on delivery in e-commerce.As an approach method used a qualitative approach based on empirical research. In this study, primary data were obtained from interviews and questionnaires. For secondary data from a literature survey. The results of this study indicate that the cash on delivery (COD) system can cause anxiety. This requires legal protection efforts to ensure the rights and obligations of the parties in online transactions, as well as more comprehensive education and stronger regulation of online transactions through e-commerce, especially the cash on delivery (COD) method. Preventive measure. e-commerces may have stricter terms of use for cash on delivery (COD) systems. Justice for the parties is realized when the parties are legally protected. Accountability efforts to the aggrieved party, especially the role of the market, must also be maintained. This is very helpful in terms of accountability if there is a problem with paying cash on delivery (COD).